Identifying Psychological and Contextual Factors Influencing Teenagers’ Future Orientation - Acar, Zeynep; Kaya, Selin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to explore and identify the psychological and contextual factors that influence the development of future orientation among teenagers. Methods and Materials: This research employed a qualitative design using semi-structured interviews with 23 adolescent participants aged 13 to 19, selected through purposive sampling from various regions in Turkey. Data collection continued until theoretical saturation was achieved. All interviews were conducted in person or online, transcribed verbatim, and analyzed thematically using NVivo software to extract categories, subcategories, and core concepts that shaped adolescents’ perceptions and behaviors related to their future orientation. Findings: Three main categories emerged from the data analysis: psychological drivers, social and environmental influences, and cognitive and planning capacities. Psychological drivers included hope and optimism, fear of failure, self-identity, motivation and ambition, and emotional regulation. Social and environmental influences comprised parental support, peer influence, school environment, socioeconomic constraints, and community expectations. Cognitive and planning capacities encompassed goal-setting skills, time perspective, decision-making ability, problem-solving skills, information-seeking behavior, and academic self-efficacy. Adolescents’ narratives reflected a complex interplay between internal motivations, emotional resilience, and external support systems in shaping their visions for the future. Direct quotations illustrated how individual aspirations were facilitated or hindered by family, peers, educational access, and cultural norms. Conclusion: The study highlights the multifaceted nature of teenagers’ future orientation and emphasizes the need for supportive family environments, inclusive educational practices, and community engagement to empower adolescents in shaping their futures.